AN OVERVIEW OF MUTUAL FUNDSAND INVESTORS' UNDERSTANDING IN RURAL AND URBAN PEOPLE INVESTMENT BEHAVIOUR AND PREFERCNCE - Madhavedi, Dr. Sudhakar; Sudhaker, P.; Apku, Malika; Srikanth, Balla (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
India is experiencing a phase of savings and investment, especially with the growth spurt in its working class. The Indian mutual fund industry is growing rapidly and this is reflected in the increase in Assets under management of various fund houses. This research paper focused on number of factors that highlights investors’ behaviour towards mutual funds and preferences of investors. The impact of various demographic and behavioural factors on investors has been studied. Design/Methodology/Approach: The study is empirical and analytical based on survey approach. It is primary data based study. Data is collected through structured questionnaire. For this purpose, we have used frequency distribution, percentages, chi square test, ANOVA, Average Score analysis and Kruskal Wallis test to prove the hypotheses. Also, Cronbach’s Alpha (CFA) is applied to measure the internal consistency of the variables. Findings: The major findings of the study reveal that demographic factors have impact on the investment decisions taken by investors. Also, it is found the aged and educated people preferred mostly safe and high return on their investment. They avoid risk. The study will be beneficial for researchers & academicians for further research, brokers, dealers, investors and share market of icials. Research Applications/Limitations: this study is helpful to identify the behaviour of investors towards mutual funds investment. Despite at most care, there has been some limitation in this study which may have impact on findings of the study. As we used convenience sampling method and only 100 samples of respondents has been selected, it is dif icult to generalize the findings to the large population. We have selected a limited area i.e. only Delhi and NCR. Also, there may be errors in development of questionnaire and data feeding. Practical Implications: Contributes to the body of knowledge on investor’s behaviours, perception n their attitude towards investment in mutual funds and its implications for investors, agencies and government for formulating policies. Originality/Value: The paper identifies a framework of relevant values and facilities that will be of use to those interested in this field